The method of specialized discursive conceptual systematizing: field practice with students of Biology-Chemistry at Oriente University - María Nila Blanch-Milhet; Alejandro A. Ramos-Banteurt; Leonardo Silva-Speck; Héctor Álvarez-Cortés (Maestro y Sociedad, 2017)
The experience presented developed in the process of the professors of Biology initial formation, starting from the application, to the practical of field, of the method discursive conceptual systematizing and its procedures: the systematic classification, the discursive conceptual disposition, the discursive production and the reflection. For it, is supported in a methodology that is structured starting from logic in the classification of the stages of the discursive conceptual progression. As particularity, the methodology has support in the focus socio cultural of knowledge, talkative, of the maternal language, quality that contributes to the improvement of the professors of Biology continuous didactic formation in the systematizing from the treatment to the systematic concepts.